Strategic factors of civil society development - Kadirov Mirsultan Batyrovich; Usarov Ikromjon Normamat oglu (Genius Journals, 2025)
In this article, civil society is considered an indicator of the combined, integrated quality indicators of social, economic, and political factors. There is a correlation between its levels and the parameters of the development of the political, legal, and economic culture of citizens. The effectiveness of the strategy and tactics of interaction between state and civil society institutions depends on the process of further improving existing laws, their rational understanding, and timely implementation. From this point of view, the harmony in the development of the political, legal, economic, and cultural life of citizens arises from the requirements of objective and subjective factors existing in society.
Keywords: humanistic imperative; manaviy; madaniy